GAMBARAN SGOT SGPT PENDERITA DEMAM BERDARAH DENGUE DI LABORATORIUM KLINIK FARMALAB SAMPANG - Ismiatus Salamah; Muhammad Sungging Pradana; Titik Sundari; Siti Nur Husnul Yusmiati (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2022)
Dengue virus infection is an infectious disease examination which is still quite high in Sampang Regency. On average, cases of dengue hemorrhagic fever spread in 22 villages from 2019-2020. The local health office noted that there were 181 cases of dengue hemorrhagic fever during January to December 2020. The locations and examinations in this study were carried out at the Farmalab Sampang Clinical Laboratory. Data collection is carried out in January 2021 to March 2021. This study aims to determine the description of liver function in patients with suspected Dengue Hemorrhagic Fever. The method used is descriptive analytic with data collection techniques based on laboratory analysis, literature study and observation. The results of the SGOT and SGPT examination showed an increase of 3-10 times in 15 respondents (75%) experiencing an increase in SGOT levels and 16 respondents (80%) SGPT.